EFFECT OF BIODIESEL/DIESEL BLEND AND TEMPERATURE ON 1-CYLINDER DIESEL FUEL INJECTION PUMP PERFORMANCE AND SPRAY PATTERN - Anis, Samsudin; Budiandono, Galuh Nur; Saputro, Danang Dwi; Zainal, Z. A. (Jurnal Bahan Alam Terbarukan, 2018)
Biodiesel as a renewable alternative energy produced from vegetable and animal oils can be used as a fuel for diesel engines. However, biodiesel has a high viscosity that affects the performance of the pump, thereby reducing diesel engine performance. One of the ways to overcome this problem is by preheating the fuel. The purpose of this study is to investigate fuel spray pattern and pump performance including capacity, head, and efficiency at various biodiesel/diesel blends (B0-B30) and preheating temperatures of B30 (30°C-70°C) at constant injection pressure. The results showed that pump performance decreased with increasing percentage of biodiesel. The weakest pump performance occurred at B30. Fuel spray pattern did not change too much, except for B30 where the spray angle decreased significantly. Better results were obtained when biodiesel blend of B30 was heated. The highest pump capacity and efficiency occurred at 50°C, while the highest pump head was at 70°C. At 60°C and 70°C, pump experienced an excessive vibration. Fuel spray angle also increased as the preheating temperature rises. The widest spray angle occurred at fuel preheating temperature of 70°C.